Direct Immunodetection of Global A‐to‐I RNA Editing Activity with a Chemiluminescent Bioassay. (28th June 2021) - Knutson, Steve D.; Arthur, Robert A.; Johnston, H. Richard; Heemstra, Jennifer M.
Abstract: Adenosine‐to‐inosine (A‐to‐I) editing is a conserved eukaryotic RNA modification that contributes to development, immune response, and overall cellular function. Here, we utilize Endonuclease V (EndoV), which binds specifically to inosine in RNA, to develop an EndoV ‐l inked i mmunos orbency a ssay (EndoVLISA) as a rapid, plate‐based chemiluminescent method for measuring global A‐to‐I editing signatures in cellular RNA. We first optimize and validate our assay with chemically synthesized oligonucleotides. We then demonstrate rapid detection of inosine content in treated cell lines, demonstrating equivalent performance against current standard RNA‐seq approaches. Lastly, we deploy our EndoVLISA for profiling differential A‐to‐I RNA editing signatures in normal and diseased human tissue, illustrating the utility of our platform as a diagnostic bioassay. Together, the EndoVLISA method is cost‐effective, straightforward, and utilizes common laboratory equipment, offering a highly accessible new approach for studying A‐to‐I editing. Moreover, the multi‐well plate format makes this the first assay amenable for direct high‐throughput quantification of A‐to‐I editing for applications in disease detection and drug development. Abstract : Adenosine‐to‐inosine (A‐to‐I) editing is a critical RNA modification, dysregulation of which is linked with autoimmune disease, neurodegenerative disorders, and several types of cancer. Here, we develop a protein‐based chemiluminescent bioassay to rapidly characterize global A‐to‐I editing signatures in normal and diseased human tissue, addressing a significant technological need for studying RNA editing and its relationship with disease.